Agromorphological Characterization of Hibiscus sabdariffa L. Collection from Burkina Faso - Ouangraoua, Wendpingrenoma Jocelyne; Traore, Renan Ernest; Kabore, Boukaré; Sawadogo, Pingawindé; Sawadogo, Mahamadou (European Scientific Journal, ESJ, 2022)
Hibiscus sabdariffa L. or roselle is an important vegetable crop in several African countries. It is rich in vitamins and minerals and is widely used in the diet of local populations in Africa, especially in Burkina Faso. However, up to now, there is no in-depth study describing roselle genetic diversity that has been carried out to assess ecotypes cultivated in Burkina Faso. Thus, this study aims to contribute to providing more insights into Hibiscus sabdariffa genetic variability in Burkina Faso through an agromorphological characterization. For this purpose, a trial was carried out using a Randomized Complete Block Design (RCBD) with three replications. 48 accessions collected from farmers were assessed. Agromorphological data collection involved 12 qualitative and 18 quantitative traits. The qualitative traits analysis showed high variability in leaf, stem, and flower color and shape. Analysis of variance (ANOVA), hierarchical cluster analysis (HCA), and principal component analysis (PCA) were performed using quantitative data. The results indicated significant differences among all genotypes for all the traits measured. The first three axes of the PCA explain 69.62% of the genetic variability. Furthermore, the results showed a high agromophological variability which is structured in three (03) groups. This variability will contribute to the enhancement and genetic improvement of Hibiscus sabdariffa.